The Nexus of Taxation for Artificial Intelligence According to the Organization of Economic Cooperation and Development and United Nations Model Tax Conventions - Mann, Jane Ross (Department of Finance and Tax, 2023)
Artificial Intelligence (AI) technology is quickly developing and is estimated to soon replace humans in specific job functions. The replacement of human jobs by AI creates two core international taxation consequences for the state in which the AI is located: (a) how artificial intelligence should be defined for tax purposes; and (b) how the income generated by AI can be taxed in the state in which the AI operates (at source). By assessing the UN (United Nations) and OECD (Organization for Economic Cooperation and Development) Model Tax Conventions, international case law and academic literature, the aim of this dissertation is to determine how states may tax AI at source. AI should be able to act independently and should be understood to be the combination of software and robotics. This dissertation aims to classify AI within the framework of the existing Model Conventions for the elimination of double taxation. The advances in technology and adoption of the new technologies exceed the pace at which national tax systems and the international tax framework can advance. Thus, seeking to fit the taxation of AI and its use within the existing framework could provide a real time solution to the tax challenges presented by the new technologies. The existing nexus for taxation is source and residency under state law, as recognised by the Model Conventions. The taxation of AI as business profits is considered under articles 7 and 5 of the Model Conventions for taxation at source. Provided states are willing to extend the current definition and provided the taxpayer controls the AI based on jurisprudence studied, it may be possible for AI to constitute a Permanent Establishment (PE). The taxation of AI for business profits does not cover the deficit in tax revenue caused by the shift of employment income to business profits, through the replacement of human employees. AI is not included in the definition of a ‘person' in the Model Conventions. AI therefore cannot presently be taxed at source based on residency. To be taxed as an employee, AI would have to classify as a “person” and a “resident” according to the Model Conventions and treaties based on the models. For these definitions to be extended, AI will need to be defined and the source and residency rules in the treaty will need to be apply to AI. AI does not fit cleanly into the provisions of the current Model Conventions for taxation at source when owned by a non-resident entity. Provided the definitions or articles can be briefly extended or interpreted widely, it would be possible for AI to be taxed under the Model Conventions and treaties based on these articles until such time as the legislation or definitions are amended.